Applying the dark diversity concept to nature conservation. Issue 1 (22nd June 2016) - Lewis, Rob J.; de Bello, Francesco; Bennett, Jonathan A.; Fibich, Pavel; Finerty, Genevieve E.; Götzenberger, Lars; Hiiesalu, Inga; Kasari, Liis; Lepš, Jan; Májeková, Maria; Mudrák, Ondřej; Riibak, Kersti; et al.
Abstract: Linking diversity to biological processes is central for developing informed and effective conservation decisions. Unfortunately, observable patterns provide only a proportion of the information necessary for fully understanding the mechanisms and processes acting on a particular population or community. We suggest conservation managers use the often overlooked information relative to species absences and pay particular attention to dark diversity (i.e., a set of species that are absent from a site but that could disperse to and establish there, in other words, the absent portion of a habitat‐specific species pool). Together with existing ecological metrics, concepts, and conservation tools, dark diversity can be used to complement and further develop conservation prioritization and management decisions through an understanding of biodiversity relativized by its potential (i.e., its species pool). Furthermore, through a detailed understanding of the population, community, and functional dark diversity, the restoration potential of degraded habitats can be more rigorously assessed and so to the likelihood of successful species invasions. We suggest the application of the dark diversity concept is currently an underappreciated source of information that is valuable for conservation applications ranging from macroscale conservation prioritization to more locally scaled restoration ecology and the management of invasive species.